An Iterative IpDFT Method for Frequency Estimation With Elimination of the Spectral Leakage - Jing Lu; Bin Wei; Kai Wang; Lu Tang; Xusheng Tang (IEEE Access)
The signal processing technology is developing rapidly, and the estimation of multi-frequency signals is becoming increasingly important in engineering applications, such as power electronics, speech signal processing, wireless communications, and so on. In this paper, we propose to use the two-point IpDFT method with the rectangular window (I2pNDFT) to estimate frequency. In the process of frequency estimation, we eliminate the spectral leakage by fully considering the influence of the positive and the negative spectra. Subsequently, we propose an interpolator for a single-frequency complex exponential signal with the objective of further enhancing the accuracy of estimation. We extend the applicability of this IpDFT method and its improvement to estimate the fundamental frequency of a signal with harmonic components. The results of the simulation demonstrate that our method is more effective than other methods.